2022
DOI: 10.2478/sjph-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of vitamin D status and dietary intake in various Slovenian populations

Abstract: Aim Vitamin D (VitD) is involved in calcium and phosphate homeostasis, bone health, and normal functioning of the immune system. VitD status is monitored using serum 25-hydroxy-vitamin D (25(OH)D) as a biomarker. Serum 25(OH)D concentrations below 30 nmol/L indicate VitD deficiency and below 50 nmol/L indicate insufficiency. VitD can be synthesised endogenously in human skin when exposed to ultraviolet B (UVB) radiation. In the absence of sufficient UVB-light exposure, VitD intake becomes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 68 publications
3
9
0
Order By: Relevance
“…It is well accepted that higher levels of anxiety during the epidemic may have caused hormone changes, resulting in increased glucose. In addition to this, many people increased sedentary behaviour, restricted their movement (22) and had lower craving control with increased snack intake during the COVID-19 lockdown (23), which was in contrast to the strengthening of protective factors against COVID-19 infection (24,25). All these factors might have predisposed pregnant women to increased fasting glucose concentration and GDM manifestation at centre by having universal early GDM screening place, therefore providing timely pharmacological treatment to those at high risk of perinatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that higher levels of anxiety during the epidemic may have caused hormone changes, resulting in increased glucose. In addition to this, many people increased sedentary behaviour, restricted their movement (22) and had lower craving control with increased snack intake during the COVID-19 lockdown (23), which was in contrast to the strengthening of protective factors against COVID-19 infection (24,25). All these factors might have predisposed pregnant women to increased fasting glucose concentration and GDM manifestation at centre by having universal early GDM screening place, therefore providing timely pharmacological treatment to those at high risk of perinatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D intake and status in Slovenia were assessed in 2017/2018 by Hribar et al ( 40 42 ). The supplementation rate in our study was increased due to the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intake of vitamin D supplements is often limited by relatively poor adherence, especially in individuals with low-socioeconomic status (lower education, marginal groups), who are at the highest risk for vitamin D deficiency. Vitamin D deficiency is a known challenging public health issue, especially during the winter months with high incidence of viral respiratory infections ( 9 ). An effective approach to improve vitamin D status in the general population could be systematic vitamin D food fortification, since it is economical, safe and decreases deficiency risk in the entire population, including people that would not use supplements ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that various population groups across Slovenia are at high risk of vitamin D insufficiency and deficiency, particularly during wintertime. All included studies reported daily intakes below the recommended level ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation